Study of interaction between metal ions and quercetin - Taiane Souza de Castilho; Tatiane Brescovites Matias; Keller Paulo Nicolini; Jaqueline Nicolini (Food Science and Human Wellness)
A displacement test based on the interaction between the flavonoid quercetin and an excess of metal chloride allows the determination of the binding constant for the reaction between quercetin and Ca2+, Mg2+ and Ni2+. The values obtained were 2.20 ± 1.77 × 103 for Ca2+, 1.37 ± 0.59 × 103 for Mg2+ and 7.03 ± 1.04 × 104 for Ni2+, and all interactions showed type 1:1 stoichiometry, as determined by titration and by the method of continuous variations (Job’s method). The complexion effect was observed qualitatively through a colorimetric change in the medium (yellow → neon yellow) and spectroscopically through a bathochromic shift in the absorption band of quercetin in the presence of metals. This investigation serves as a tool for the development and testing of materials capable of capturing toxic metal ions or favoring the absorption of beneficial ions (in relation to the human metabolism) through the construction of efficient bioorganic systems. The results reported herein allow understanding of this detection system, indicating the following ascending order of the binding constants (Mg2+ < Ca2+ < Al3+ < Ni2+). Keywords: Binding constants, Quercetin, Antioxidant properties